2006
DOI: 10.1093/annonc/mdl296
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of adjuvant endocrine treatment according to PR and HER-2 status in early breast cancer

Abstract: Patients with estrogen receptor (ER)+/progesterone receptor (PR)- and/or HER-2 overexpressing breast carcinomas may derive lower benefit from endocrine treatment. We examined retrospectively data from 972 breast cancer patients who received tamoxifen (725), tamoxifen + Gn-RH analogs (127) and aromatase inhibitors (120) as adjuvant treatments. ER+/PR- versus ER+/PR+ tumours were characterised by larger size (P = 0.001), higher tumour grade (P = 0.001), higher Ki-67 expression (P = 0.001) and lower mean ER (P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 21 publications
2
15
0
1
Order By: Relevance
“…If there is elevated CA 15-3 levels in the patients with isolated bone metastasis, then patients had poor metastatic free survival and overall survival in this study. In addition to the CA 15-3 levels, the Her2/neu overexpression is associated with aggressive clinical and pathological features [27]. Clinically, a patient whose Her2/new strongly positive tends to have a poor prognosis and a decreased survival time [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is elevated CA 15-3 levels in the patients with isolated bone metastasis, then patients had poor metastatic free survival and overall survival in this study. In addition to the CA 15-3 levels, the Her2/neu overexpression is associated with aggressive clinical and pathological features [27]. Clinically, a patient whose Her2/new strongly positive tends to have a poor prognosis and a decreased survival time [28].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, a patient whose Her2/new strongly positive tends to have a poor prognosis and a decreased survival time [28]. PR status defines a subset of tumor with distinctive pathological characteristic and may help selecting those patients who derive the greatest benefit from endocrine adjuvant treatment [27]. When the survival in the patients with isolated bone metastasis is evaluated, it is demonstrated that the positiveness in PR status had positive and Her2/neu overexpression had negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…A weakness in our study is the median FU period which consisted of 3.5 years only and which allows us only short-term DFI interpretations. Others have referred to ER and PR as only being short-term prognostic factors whereas little data are available on HER-2 as a prognostic factor beyond five years of FU [6,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that the benefit of tamoxifen is less for ER-positive/PR-negative tumors than for ER-positive/PR-positive tumors in both adjuvant and palliative settings (Bardou et al 2003;Liu et al 2010;Ponzone et al 2006;Ravdin et al 1992;Stendahl et al 2006). However, there are conflicting reports on the value of PR status, with some studies suggesting that it may not provide additional prognostic information for ER-positive breast cancers (Early Breast Cancer Trialists' Collaborative Group 2005;Olivotto et al 2004;Paik et al 2005).…”
Section: Introductionmentioning
confidence: 99%